High Salt Electrolyte Solutions Challenge the Electrochemical CO2 Reduction Reaction to Formate at Indium and Tin Cathodes - Aykut Kas; Dr. Paniz Izadi; Prof. Dr. Falk Harnisch (ChemElectroChem, 2023)
Abstract Formate is a promising product of the electrochemical CO2 reduction reaction (eCO2RR) that can serve as feedstock for biological syntheses. Indium (In) has been shown as a selective electrocatalyst of eCO2RR with high coulombic efficiency (CE) for formate production at small scale at biocompatible non‐halophilic that is low salt conditions. Ohmic losses and challenges on potential/current distribution arise for scaling‐up, where higher salt loads are advantageous for minimizing these. Higher salt concentration within the solution or halophilic conditions also enable the use of halophilic biocatalysts. We optimized eCO2RR with halophilic media by introducing tin (Sn) as a more sustainable alternative to In. At 3 % NaCl providing a catholyte conductivity ( κS) of 70 mS cm−1, the maximum specific formate production rates (rformate) of 0.143±0.030 mmol cm−2 h−1 and 0.167±0.027 mmol cm−2 h−1 were achieved at In and Sn electrocatalysts, respectively. Decrease in rformate and CE, in addition to higher variation between replicates was observed with further increase in NaCl concentration above 3 % ( κS >70 mS cm−1) up to 10 % ( κS =127 mS cm−1). This study sets the foundation for integrated microbial synthesis by halophiles.